2022
DOI: 10.3389/fphys.2022.943108
|View full text |Cite
|
Sign up to set email alerts
|

The influence of blue light on sleep, performance and wellbeing in young adults: A systematic review

Abstract: Introduction: Blue light from electronic devices has a bad reputation. It has a wavelength which may influence our circadian rhythm and cause bad sleep. But there are other aspects of blue light exposure which are often overlooked, for example, it may influence performance and wellbeing. However, few resources summarize its effects systematically. Therefore, the goal of this systematic review was to distil the present evidence on blue light exposure and its influence on sleep, performance and wellbeing and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 77 publications
2
21
0
3
Order By: Relevance
“…Experimental studies on the effects of SWL exposure on alertness or sleepiness have shown conflicting results. This is evident from the most recent systematic reviews (Souman et al 2018; Xu and Lang 2018; Mu et al 2022; Silvani et al 2022) assessing the effect of SWL on these outcomes. Mu et al (2022) performed the only review with a meta-analysis.…”
Section: Physiological Effects Of Swl Exposurementioning
confidence: 99%
See 3 more Smart Citations
“…Experimental studies on the effects of SWL exposure on alertness or sleepiness have shown conflicting results. This is evident from the most recent systematic reviews (Souman et al 2018; Xu and Lang 2018; Mu et al 2022; Silvani et al 2022) assessing the effect of SWL on these outcomes. Mu et al (2022) performed the only review with a meta-analysis.…”
Section: Physiological Effects Of Swl Exposurementioning
confidence: 99%
“…In summary, the results by Souman et al (2018) and Xu and Lang (2018) indicate that nighttime exposure to SWL may influence alertness slightly more than daytime exposure. Silvani et al (2022) only reviewed studies that examined effects of SWL but did not specify the time of day of the exposures. They found that more studies reported alerting effects vs. no effects, and this was similar for both subjective and objective alertness.…”
Section: Physiological Effects Of Swl Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…Healthcare workers caring for the baby on phototherapy are constantly exposed to blue light and thereby its side effects. Altered circadian rhythm results in disruption in the sleep-wake cycle affecting healthcare providers particularly working during the night shift [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%